Teachers Leadership and Work Environment That Influence the Effectiveness of Teachers Performance in Secondary School Level - Buapong, Pakamass; Chienwattanasook, Krisada (Journal of Management Science Nakhon Pathom Rajabhat University, 2021)
This study aimed at studying the level of teacher’s leadership and work environment that influence the effectiveness of teacher’s performance. This research collected 186 secondary school teachers. The research instrument was a questionnaire. The data was analyzed by using descriptive statistics such as frequency, percentage, average, deviation, and multiple regression analysis. The result shows that teacher’s leadership for change has the highest influence on work performance among three aspects. In terms of work environment, instructional program management, and instructional model had the greatest influence on performance. of the teacher with statistical significance at the 0.05 level, the equation had 58.00 percent predictive power. The work environment influenced the teacher's performance, including job-specific characteristics, security, and job supervision. teacher's work with statistical significance at the 0.05 level, the equation had 46.20% predictive power. Article history: Received 11 February 2020 Revised 20 Murch 2020 Accepted 27 Murch 2020 SIMILARITY INDEX = 0.00 %